Digital tool assessment for the community management of patients with pulmonary tuberculosis in Yiwu city, China: evidence from real world data in 2020 - Zhou, Lin; Zhou, Yuli; Ding, Yunfang; Peng, Ying; Wang, Wei; Chen, Bin; Gong, Shuiying; Liu, Kui; Dong, Xuanjun (Frontiers in Public Health, 2024)
Background High-quality medication compliance is critical for the cure of pulmonary tuberculosis (PTB); however, the implementation of directly observed treatment (DOT) under direct interview still faces huge difficulties. Assessment of the effect of digital tool during community management has not been performed in eastern China. Methods All drug-sensitive PTB cases notified in Yiwu city from June to December 2020 were divided into the routine group and digital tool group based on patients’ willingness. The variables influencing the on-time completion level of home visits, medication adherence and treatment outcomes were estimated. Results A total of 599 eligible patients were enrolled, with 268 participating in the routine group and 331 using a digital tool. Most participants were men (n = 357, 59.6%), and nearly all were new cases (n = 563, 94.0%). Participants’ mean age was 44.22 ± 20.32 years. There were significant differences in age, diagnostic type, and source of patients between the two groups. During the study period, the digital tool group had a higher on-time completion rate of home visits (91.5% vs. 82.5%) and medication adherence rate (94.3% vs. 89.6%) than the routine group, whereas there was no significant difference in the treatment success rate between the two groups (91.2% vs. 86.8%). Multivariate logistic regression analysis demonstrated that the digital tool group showed a more positive function in the on-time completion status of home visits, with an adjusted odds ratio of 0.41 (95% confidence interval: 0.25–0.70). Conclusion Digital tools can be employed to improve the on-time completion rate of home visits in Yiwu city. Further large-scale studies that use digital tools for community management are warranted.